Cellphone Masts deployment in Brazil: Case Studies and Assessment of the Judicial Disputes between Governmental Entities - Veronese, Alexandre (Law, State and Telecommunications Review, 2013)
Purpose ”“ The paper details judicial disputes over telecommunications regulation and environmental issues regarding mobile phone infrastructure in the nowadays Brazil. It shows how such typical conflicts happened in comparison with some international cases. Methodology/approach/design ”“ The research applied comparative methods and qualitative analysis, by pinpointing international cases in order to enlighten the Brazilian situation, and its dispute resolution system. The comparison demonstrates that it was public entities and authorities that brought conflicts in the Brazilian judicial system, instead of civil society groups. Findings ”“ Such issues related to the mobile phone infrastructure do not give rise to social mobilization in Brazil, neither through associations, nor through public debate. That agenda is captured by large by public entities and authorities as diagnosed by the Brazilian judicialization of politics studies (Werneck Vianna et al., 1999). Practical implications ”“ The paper enlightens a phenomenon scarcely researched in Brazil that has consequences over utilities and infrastructure public policies. It is important for the national development debate also due to its impact on licensing and technical precaution costs. Originality/value ”“ The paper aims to fill a gap in the literature, as well as to stimulate a methodological option by building bridges among legal studies analyses, sociology, and other social sciences.